IFNAR signaling of neuroectodermal cells is essential for the survival of C57BL/6 mice infected with Theiler’s murine encephalomyelitis virus - Melanie Bühler; Dandan Li; Lin Li; Sandra Runft; Inken Waltl; Andreas Pavlou; Ulrich Kalinke; Malgorzata Ciurkiewicz; Jochen Huehn; Stefan Floess; Andreas Beineke; Wolfgang Baumgärtner; et al. (Journal of Neuroinflammation, 2023)
Abstract Background Theiler’s murine encephalomyelitis virus (TMEV) is a single-stranded RNA virus that causes encephalitis followed by chronic demyelination in SJL mice and spontaneous seizures in C57BL/6 mice. Since earlier studies indicated a critical role of type I interferon (IFN-I) signaling in the control of viral replication in the central nervous system (CNS), mouse strain-specific differences in pathways induced by the IFN-I receptor (IFNAR) might determine the outcome of TMEV infection. Methods Data of RNA-seq analysis and immunohistochemistry were used to compare the gene and protein expression of IFN-I signaling pathway members between mock- and TMEV-infected SJL and C57BL/6 mice at 4, 7 and 14 days post-infection (dpi). To address the impact of IFNAR signaling in selected brain-resident cell types, conditional knockout mice with an IFNAR deficiency in cells of the neuroectodermal lineage (NesCre±IFNARfl/fl), neurons (Syn1Cre±IFNARfl/fl), astrocytes (GFAPCre±IFNARfl/fl), and microglia (Sall1CreER±IFNARfl/fl) on a C57BL/6 background were tested. PCR and an immunoassay were used to quantify TMEV RNA and cytokine and chemokine expression in their brain at 4 dpi. Results RNA-seq analysis revealed upregulation of most ISGs in SJL and C57BL/6 mice, but Ifi202b mRNA transcripts were only increased in SJL and Trim12a only in C57BL/6 mice. Immunohistochemistry showed minor differences in ISG expression (ISG15, OAS, PKR) between both mouse strains. While all immunocompetent Cre-negative control mice and the majority of mice with IFNAR deficiency in neurons or microglia survived until 14 dpi, lack of IFNAR expression in all cells (IFNAR−/−), neuroectodermal cells, or astrocytes induced lethal disease in most of the analyzed mice, which was associated with unrestricted viral replication. NesCre±IFNARfl/fl mice showed more Ifnb1, Tnfa, Il6, Il10, Il12b and Ifng mRNA transcripts than Cre−/−IFNARfl/fl mice. IFNAR−/− mice also demonstrated increased IFN-α, IFN-β, IL1-β, IL-6, and CXCL-1 protein levels, which highly correlated with viral load. Conclusions Ifi202b and Trim12a expression levels likely contribute to mouse strain-specific susceptibility to TMEV-induced CNS lesions. Restriction of viral replication is strongly dependent on IFNAR signaling of neuroectodermal cells, which also controls the expression of key pro- and anti-inflammatory cytokines during viral brain infection.